Gender equality in public services chasing the dream - Conley, Hazel; Page, Margaret (Routledge, 2015)
The provision of state funded and democratically accountable care services represents one of the most potentially transformative advances in gendered social relations and equality for women by 'defamilizing' care and providing paid work. But the cost of providing these services, which women have access to them and how they should be provided are always at the forefront of debate, especially during economic crises